A new species of Pseudorhynchelmis Hrabě, 1982 (Clitellata: Lumbriculidae) from Lake Baikal, with re-descriptions of P. parva and P. olchonensis - Martin, Patrick; Kaygorodova, Irina (Zootaxa, 2008)
The recent rediscovery of specimens of the Baikalian lumbriculid Pseudorhynchelmis olchonensis (Burow et Koshow, 1932) led to the re-examination of (1) Michaelsen’s hundred-year-old type specimens of Lycodrilus parvus, assumed, for a long time, to have been wrongly attributed to the Tubificidae instead of the Lumbriculidae, and of (2) type specimens used by Hrabě (1982) for his redescription of Lycodrilus parvus and its combination with the newly, subsequently created genus Pseudolycodrilus Hrabě, 1982. Surprisingly enough, the original description of Pseudolycodrilus parvus (Michaelsen, 1905) proved to be based on a mixing of two different species, P. parva and Pseudorhynchelmis semernoyi sp. nov., both of which are herein assigned to the recently re-established genus Pseudorhynchelmis Hrabě, 1982. As a result, the genus Pseudolycodrilus is invalidated and must be considered as a synonym of Pseudorhynchelmis. P. parva and P. olchonensis are re-described on the basis of neotypes and lectotypes, respectively. P. semernoyi sp. nov. is distinguished from other Pseudorhynchelmis by having a conical prostomium, a well-marked clitellum with a honeycomb-like structure, and genital, sucker-like papillae, associated with penial setae. The description of the new species P. semernoyi, plus a re-evaluation of P. olchonensis, called into question the taxonomical status of Pseudorhynchelmis dissimilis (Semernoy, 2004). This study provides new examples of genital setae in the Lumbriculidae although this character remains exceptional within the family.